Analisis Pendapatan dan Tingkat Kesejahteraan Rumah Tangga Petani Padi Sawah (Oryza Sativa L.) di Nagari Kambang Utara Kabupaten Pesisir Selatan - Putra, Iksan Dwi; Amnilis; Gusriati (Jurnal Research Ilmu Pertanian, 2023)
The purpose of this study was to analyze the Income and Welfare of Rice Farmers' Households (Oryza Sativa L) in Nagari Kambang Utara, Pesisir Selatan Regency. This research was conducted from March to April 2020. The research method used is a survey method with a population of 180 people and a sample of 64 people. Data were analyzed, qualitatively and quantitatively descriptively. The results showed that the average income received by rice farmers in North Kambang Nagari, Pesisir Selatan Regency, was Rp. 16,215,639,-/MT and the profit received by farmers is Rp. 13,467,021,-/MT. Based on the R/C ratio analysis, it can be said that lowland rice farming in the research location is profitable because it has an R/C ratio value greater than one. The R/C value of the total cost ratio is 2.6 with the level of welfare including the category of less prosperous households with a GSR value of 1.68 (> 1).